2005
DOI: 10.1063/1.1849853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two-dimensional electron gas on the optical properties of InAs/GaAs quantum dots in modulation-doped heterostructures

Abstract: The Shubnikov–de Haas data showed that the carrier density of two-dimensional electron gas (2DEG) in the GaAs active region containing InAs quantum dot (QD) arrays embedded between modulation-doped Al0.25Ga0.75As/GaAs heterostructures increased with increasing doping concentration in the modulation layer. The transmission electron microscopy images showed that the sizes of the self-assembled InAs vertically stacked QD arrays inserted in the GaAs did not change significantly with increasing carrier density of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These experiments are sensitive to deformations of the potential energy landscape of the 2DEG through local density modifications and charge scattering from the SAQDs. Limited studies have also examined the effect of the 2DEG on the optical properties of the SAQDs and shown that for barriers of 30 nm, ensemble emission spectra are largely unperturbed [50,51]. In addition, transport through the 2DEG has been used to detect charge occupation in the SAQD layer [52][53][54][55][56][57], and enable single photon detection by extension [58,59].…”
Section: Relation To Other Approaches In Quantum Coherent Semiconduct...mentioning
confidence: 99%
“…These experiments are sensitive to deformations of the potential energy landscape of the 2DEG through local density modifications and charge scattering from the SAQDs. Limited studies have also examined the effect of the 2DEG on the optical properties of the SAQDs and shown that for barriers of 30 nm, ensemble emission spectra are largely unperturbed [50,51]. In addition, transport through the 2DEG has been used to detect charge occupation in the SAQD layer [52][53][54][55][56][57], and enable single photon detection by extension [58,59].…”
Section: Relation To Other Approaches In Quantum Coherent Semiconduct...mentioning
confidence: 99%
“…[1][2][3][4] On the other hand, zero dimensional structures such as self-assembled QDs have recently attracted great interest both theoretically and experimentally [5][6][7][8] thanks to their optical and electrical properties. [22][23][24][25] These studies [22][23][24][25] have shown that the photoluminescence ͑PL͒ intensity of InAs/GaAs QDs is significantly enhanced by the modulation doped AlGaAs/GaAs heterostructure. The optical and electrical properties of InAs/GaAs QDs will be significantly modified when these QDs are inserted near the AlGaAs/GaAs heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to study the effect of the combination of these two low dimensional systems, ͑2DEG and QDs͒. Kim et al 24 demonstrated a blueshift when the carrier density of the 2DEG increases. A lot of work has already been done to study the transport and electrical properties of a 2DEG in the vicinity of QDs.…”
Section: Introductionmentioning
confidence: 99%